IDENTITAS DIRI REMAJA AKHIR PENGGUNAAN KNALPOT BRONG PADA KOMUNITAS ASDI HOME GARAGE - Syah Daviq Alfarizi; Andys Tiara; Mustiawan (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) - Universitas Muhammadiyah Cirebon, 2026)
Late adolescence is an important stage in the development of self-identity, as individuals begin to understand themselves through various experiences and social interactions. One of the social environments that contributes to this process is the automotive community, including communities of loud exhaust (knalpot brong) users. This study aims to examine the process of self-identity formation among late adolescents who use loud exhaust systems in the Asdi Home Garage (AHG) community. The study employed a qualitative approach using a case study method. Three informants were selected through purposive sampling, consisting of active AHG members aged 20–24 years who use loud exhaust systems. Data were collected through in-depth interviews, observation, and a literature review, and were analyzed using the Miles and Huberman data analysis model. The findings indicate that the participants' self-identity was formed through the processes of social categorization, social identification, and social comparison. Loud exhaust systems and other community attributes were interpreted as symbols that strengthened members' sense of belonging, solidarity, and social identity. This study offers a different perspective by examining loud exhaust use not merely as an issue of legal violation or noise pollution, but also as an important element in the process of self-identity formation within an automotive community.